1972
DOI: 10.1002/aja.1001330205
|View full text |Cite
|
Sign up to set email alerts
|

The postnatal development of the retina in the normal and rodless CBA mouse: A light and electron microscopic study

Abstract: The postnatal development of the retina in control (CBA/S) and rodless (CBA/Ki) mice was studied by light and electron microscopy. In the control mice, the major increase in retinal thickness occurs between birth and seven days. The inner and outer segments begin to grow into the optic ventricle between seven and ten days with their most rapid growth occurring between 12 to 15 days; by 35 days the retina appears mature. During development, the nuclear layers become thinner while the optic ventricle (layer of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(66 citation statements)
references
References 22 publications
8
58
0
Order By: Relevance
“…Degeneration becomes evident in the outer segments first as early as postnatal day 8, followed by the inner segments and photoreceptor cell bodies (Sanyal and Bal, 1973). Degeneration occurs so rapidly that only a thin layer of scattered rod photoreceptor cell bodies (lacking outer segments) remains at postnatal day 15, and the rod cell bodies disappear completely from the central retina by 36 d (Caley et al, 1972;Carter-Dawson et al, 1978), leading to blindness. Behavioral measurement to assess vision capabilities using the visual cliff task showed that rd1 mice were no longer capable of pattern recognition shortly after 40 d of age (Nagy and Misanin, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…Degeneration becomes evident in the outer segments first as early as postnatal day 8, followed by the inner segments and photoreceptor cell bodies (Sanyal and Bal, 1973). Degeneration occurs so rapidly that only a thin layer of scattered rod photoreceptor cell bodies (lacking outer segments) remains at postnatal day 15, and the rod cell bodies disappear completely from the central retina by 36 d (Caley et al, 1972;Carter-Dawson et al, 1978), leading to blindness. Behavioral measurement to assess vision capabilities using the visual cliff task showed that rd1 mice were no longer capable of pattern recognition shortly after 40 d of age (Nagy and Misanin, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…The development of potential treatments is difficult using this mouse well as a loss of photoreceptor axon terminals at P20 (Barhoum et al, 2008). Therefore, the nuclear and plexiform layers in the retina have established their mature state (Caley et al, 1972) before the onset of significant photoreceptor loss. Degeneration of photoreceptors follows a clear gradient from the central to the peripheral regions of the retina, with a delay of 2-3 days observed between these regions (Gargini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We then determine the maximum amount of Mn 2+ that can be used to trace pathways without long-lasting damage to vision, as assessed by both physiological and morphological criteria. Next, we test whether Mn 2+ transport is dependent on electrical activity by tracing this pathway in a blind mouse, the inbred CBA strain, lacking active photoreceptors (Caley et al, 1972). This mouse carries the rd mutation and has no rod light detector cells in the retina (Bowes et al, 1990).…”
Section: Introductionmentioning
confidence: 99%